اتجاهات المعلمين حول عملية تكييف المناهج للطلاب الصم وضعاف السمع ومعيقات تطبيقه وفق مجموعة من المتغيرات في مدينة جدة - الثقفي، بيان طالب; الشهراني، محمد بن مبارك بن مشيط (المؤسسة العربية للتربية والعلوم والآداب, 2022)
هدفت الدراسة الحالية إلى الكشف عن اتجاهات المعلمين حول عملية تكييف المناهج للطلاب الصم وضعاف السمع ومعيقات تطبيقه، وفق مجموعة من المتغيرات في مدينة جدة. قامت الباحثة بتطبيق استبيان (من إعداد الباحثة) لقياس الاتجاهات والمعيقات حول عملية تكييف المناهج للطلاب الصم وضعاف السمع، على عينة مكونة من (148) معلما ومعلمة من معلمي معاهد الأمل وبرامج الدمج بمدينة جدة. تكونت عينة الدراسة من (49) معلما، و(99) معلمة، واعتمدت على المنهج الوصفي المسحي. أظهرت النتائج مستوى مرتفع جدا لاتجاهات المعلمين حول عملية تكييف المناهج على جميع الأبعاد (المحتوى، الأهداف، الأنشطة، طرق التدريس، والتقويم) للطلاب الصم وضعاف السمع في مدينة جدة. وتبين كذلك أن مستوى المعوقات التي تحول دون تكييف مناهج الطلاب الصم وضعاف السمع من وجهة نظر المعلمين في مدينة جدة كبيرة جدا. كما أظهرت النتائج أيضا وجود فروق ذات دلالة إحصائية في اتجاهات المعلمين حول عملية تكييف المناهج على بعد (المحتوى، طرق التدريس، التقويم، والدرجة الكلية) وفي معيقات تطبيقه للطلاب الصم وضعاف السمع باختلاف متغير الجنس لصالح المعلمين الذكور. كذلك وجدت فروق ذات دلالة إحصائية في اتجاهات المعلمين حول عملية تكييف المناهج على بعد (المحتوى، الأهداف، التقويم، والدرجة الكلية) وفي معيقات تطبيقه للطلاب الصم وضعاف السمع باختلاف متغير البيئة التعليمية لصالح معلمي معاهد الأمل. بينما لم يتم العثور على فروق ذات دلالة إحصائية في اتجاهات المعلمين حول عملية تكييف المناهج ومعيقات تطبيقه للطلاب الصم وضعاف السمع باختلاف متغيري (المؤهل العلمي، والمرحلة الدراسية للمتعلمين). وفي الختام أوصت الباحثة بإعداد تصور مقترح لتكييف وحده في المنهج باستخدام طرق واستراتيجيات حديثة مناسبة للصم وضعاف السمع والتعرف على مدى فاعليتها.
The current study aimed to explore teachers' attitudes about the process of adapting curricula for deaf and hard of hearing (DHH) students, and the obstacles to its application, according to a set of variables in the city of Jeddah. The researcher applied a questionnaire (prepared by the researcher) to measure attitudes and obstacles regarding the process of adapting curricula for (DHH) students, on a sample of (148) male and female teachers of the Al-Amal Institutes and inclusion programs in Jeddah. The study sample consisted of (49) male and (99) female teachers, and it relied on the descriptive survey method. The results showed a very high level of teachers' attitudes about the process of adapting curricula on all dimensions (content, objectives, activities, teaching methods, and assessment) for (DHH) students in Jeddah. It was also found that the level of obstacles that prevent the adaptation of the curricula of (DHH) students from teachers’ viewpoint in the city of Jeddah is very large. The results also showed that there were statistically significant differences in teachers' attitudes about the process of adapting curricula on (content, teaching methods, evaluation, and total score) and in the obstacles to its application for (DHH) students according to the gender variable in favor of male teachers. There were also statistically significant differences in teachers' attitudes about the process of adapting curricula in (content, objectives, evaluation, and total score) and in the obstacles to its application for (DHH) students according to the variable of the educational environment in favor of Al-Amal Institutes’ teachers. While no statistically significant differences were found in teachers' attitudes about the process of adapting curricula and the obstacles to its application for (DHH) students according to the two variables (qualification and the educational stage). In conclusion, the researcher recommended the preparation of a proposed scenario to adapt it alone in the curriculum using modern methods and strategies suitable for (DHH) and to identify the extent of their effectiveness.
Keywords: الإعاقة السمعية -- العملية التعليمية -- الأساليب التدريسية -- المناهج الدراسية -- مدينة جدة